Kekuatan Hukum Atas Akta Pemberian Hak Tanggungan yang Tidak Mencantumkan Kuasa Pihak Perbankan - Muhammad Yasmin; Supriadi Jufri; Ika Fitria; Afrilia Cahyani (Journal on Education, 2023)
This study aims to analyze and criticize the position of APHT which does not include the power of of attorney for the banking party and PPAT's responsibility for its negligence in making APHT, which in the comparison of the deed does not include the power of the bank. This research is normative . The results of the study indicate that the making of a deed by PPAT is obliged to make APHT according to the guidelines for filling procedures based on Article 96 number (1) letter f as attached to VIb PERKABAN 8/2012, an error due to PPAT's negligence in making APHT in accordance with the author's case study caused The APHT made by PPAT XX Makassar City became null and void, because the APHT contained an inconsistency in the filling instructions which did not include a power of attorney from the bank, compared to APHT as the legal basis for acting on behalf of the directors of a banking company. The aggrieved party can also submit a complaint to the PPAT Regional Supervisory and Supervisory Council (MPPD), so that the PPAT concerned is given sanctions for negligence committed against the APHT he made.